Promoting multidisciplinary research to improve goat production systems in Morocco - Nassif F.; El Amiri B. (Economic, social and environmental sustainability in sheep and goat production systems, 2011)
In Morocco, goat keeping is one of the most ancient economic activities in communities of the High and Middle Atlas Mountains. Goats may be the main all year round source of income and contribute to the satisfaction of primary nutritional requirements of rural livelihoods. Studies on the technical, environmental, social, economic, and policy aspects of the goat sector are scanty. A case study analysis of the goat production systems in Aït Bazza community in the Middle Atlas has revealed interesting insights on goat farmers' management practices, their marketing behaviour and constraints. One of the lessons learned is the complexity of the goat production sector. Goat farmers' socio-economic conditions and perceptions are complicated by layers of environmental and market limitations. The study concludes by demonstrating the necessity for research along disciplinary lines as well as multidisciplinary research in major goat producing areas of Morocco. The latter can help with developing a better understanding of the multifaceted nature of sustainable goat production systems.
7. Proceedings of the International Seminar of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2010/11/10-12, Zaragoza (Spain)